Peusijuk, Sarana Silaturahmi dan Sedekah Makanan untuk Keberkahan; Studi Sosialisasi Agama pada Masyarakat - Abubakar; Suci Andayani; Dahlia Ules; Dilva Cantika; Gebrina Amirah Ramadhana; Muhammad Abiyu Ikbar; Muhammad Arsyikal; Nafisah Rizkita; Nazira Masyhurah; Putri Asri Zalfarah (Jurnal Sociohumaniora Kodepena (JSK), 2026)
This study aims to analyze the tradition of Peusijuk as a medium of religious socialization, social interaction, and food almsgiving (sedekah makanan) within Acehnese society. Peusijuk is not merely a cultural ritual but also represents the internalization of religious, social, and nutritional values that contribute to social harmony and collective well-being. This research employed a qualitative descriptive approach through observation, interviews, and documentation. The findings indicate that Peusijuk plays a significant role in strengthening social bonds, transmitting religious values, and practicing food sharing as a form of almsgiving. From a nutrition perspective, food sharing during Peusijuk contributes to the fulfillment of basic nutritional needs and reflects communal awareness of food security.